Longitudinal Pancreaticojejunostomy for Pancreaticodigestive Tract Anastomotic Stricture After Pancreaticoduodenectomy. Issue 3 (23rd November 2021) - Matsumoto, Ippei; Kamei, Keiko; Kawaguchi, Kohei; Yoshida, Yuta; Matsumoto, Masataka; Lee, Dongha; Murase, Takaaki; Satoi, Shumpei; Takebe, Atsushi; Takeyama, Yoshifumi
Abstract: Aim: Pancreaticodigestive tract anastomotic stricture is a long‐term complication of pancreticoduodenectomy (PD). However, optimal treatment has not yet been defined. We conducted longitudinal pancreaticojejunostomy (LPJ) in symptomatic patients with anastomotic stricture after PD. This study aimed to evaluate the efficacy of this procedure. Methods: Pancreticoduodenectomy was performed in 605 patients at our institution between January 2005 and April 2020. Of these, 15 patients (2.5%) developed symptomatic pancreaticodigestive tract anastomotic stricture after PD. Three patients were referred to our institution owing to recurrent pancreatitis with anastomotic stricture after PD. LPJ was indicated for these 18 patients, and they were enrolled in this study. Results: The median time from the initial operation to LPJ was 2.0 y. Preoperative clinical presentations included obstructive pancreatitis in 10 patients, a rapid deterioration of glucose tolerance in nine, and severe steatorrhea in two. Surgical morbidity ≥grade III defined by the Clavien–Dindo classification was not observed. After LPJ, preoperative symptoms improved in 16 patients (89%) during a median follow‐up of 39 mo. Nine of the 10 patients with obstructive pancreatitis achieved complete pain relief. All nine patients with a rapid deterioration of glucose tolerance showed improved endocrine function. Daily insulin requirement was significantly decreased after LPJ (11.6 ± 3.3 vs 3.4 ± 4.3 units, P = .0239). Four of the seven patients who required insulin injections were free of insulin after LPJ. Conclusion: LPJ is a safe and effective surgical procedure for symptomatic patients with stricture of the pancreaticodigestive tract anastomosis after PD. Abstract : Pancreaticodigestive tract anastomotic stricture is one of the long‐term complications after pancreticoduodenectomy. We report the efficacy of longitudinal pancreaticojejunostomy for symptomatic patients with anastomotic stricture after PD.